2020
DOI: 10.1007/s12526-019-01036-9
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography of epibenthic assemblages in the central Beaufort Sea

Abstract: Benthic communities change drastically in both biomass and community structure with increasing water depth on a global scale, attributed to a combination of food supply, environmental drivers, as well as physiological and competitive capacities. In the Arctic, benthic biogeographic patterns are additionally thought to be a result of the region's glaciation history. Here, we investigate gross epibenthic biomass and assemblage structure turnover with water mass from coastal to bathyal depths from 136 beam trawl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 101 publications
2
8
1
Order By: Relevance
“…Such a shift was for example seen in the abrupt appearance of the deep-dwelling glass shrimp Pasiphaea tarda beyond the shelf break. Also, the ophiuroid Ophiopleura borealis was absent from the slope but abundant on the shelf in the present study, though this distribution pattern appears to contradict Piepenburg et al (1997b) and Ravelo et al (2015Ravelo et al ( , 2020 who found that O. borealis was absent from the shelf but present on the slope near our study area and in the Beaufort Sea, respectively.…”
Section: Slope Communitiescontrasting
confidence: 96%
See 3 more Smart Citations
“…Such a shift was for example seen in the abrupt appearance of the deep-dwelling glass shrimp Pasiphaea tarda beyond the shelf break. Also, the ophiuroid Ophiopleura borealis was absent from the slope but abundant on the shelf in the present study, though this distribution pattern appears to contradict Piepenburg et al (1997b) and Ravelo et al (2015Ravelo et al ( , 2020 who found that O. borealis was absent from the shelf but present on the slope near our study area and in the Beaufort Sea, respectively.…”
Section: Slope Communitiescontrasting
confidence: 96%
“…While the three slope locations were geographically far apart, their communities were rather similar, with relatively similar depth and hydrography (Table 7), a finding similar to slope communities along the Arctic interior Beaufort Sea (Ravelo et al 2020). Abundances were also similarly low at these slope locations, consistent with the decreasing amount of food particles that reach the seabed with increasing depth (Riser et al 2008) in the study area.…”
Section: Slope Communitiessupporting
confidence: 61%
See 2 more Smart Citations
“…Shifts in relative dominance of certain indicator species (in this case two brittle star species) in the Alaskan Beaufort Sea between the 1970s and 2010s were also thought to be related to the strength of the boundary current, a transport pathway of pelagic larvae for the species more common in the CS (Ravelo et al, 2015). Whether any of these benthic shifts would perpetuate into the basin is doubtful given Pacific-affinity species are virtually absent in deep slope and basin areas of the CS and BG margins today and seem to have limited depth tolerance (Zhulay et al, 2019;Ravelo et al, 2020). As with holozooplankton, range expansions of largely immobile benthic animals are limited by residence time of their pelagic larvae on the CS shelf.…”
Section: Effects Of Pacification On Consumer Trophic Levelsmentioning
confidence: 99%